Structural basis for functional interactions in dimers of SLC26 transporters - Yung-Ning Chang (Nature Portfolio, 2019)
The SLC26 family of transporters maintains anion equilibria in all kingdoms of life. Here, the authors resolve the structure of an SLC26 dimer embedded in a lipid membrane and characterize it by PELDOR/DEER distance measurements, biochemical studies with MD simulations and spin-label ensemble refinement.